Social marketing to improve healthy dietary decisions: Insights from a qualitative study in Mexico. Issue 3 (3rd June 2014) - Carrete, Lorena; Arroyo, Pilar
Abstract : Purpose: – The purpose of this research is to improve the understanding of drivers and inhibitors of healthy diet behaviors in the context of an emerging economy, such as Mexico, with a severe problem of overweight and obesity. The theory of planned behavior (TPB) and protection motivation theory (PMT) provided the theoretical background for this study. Design/methodology/approach: – A qualitative approach was used, given the limited amount of information available on consumers' motivations to change behavior. In-depth interviews with experts in nutrition and four focus groups with consumers from two segments were performed to collect information. Thematic analysis was used to analyze information. Findings: – PMT provided a better explanation of current dietary behavior; the positive attitudes that, according to TPB, are the immediate antecedent of behavior offered a poor explanation for autoreported behaviors. Results indicate that perceived low self-efficacy and high costs prevent change of behavior. Meanwhile, low vulnerability and severity among younger consumers adds to the low intention to adopt a healthier diet. In general, sensorial attributes of products, such as texture, flavor, color, smell and appearance, prevail over nutritional attributes. Practical implications: – The outline of a social marketing program is suggested after the research findings. This program emphasizes prevention and is intended to complement governmental policies designed to modify the environment to facilitate access to healthy food. Originality value: – Social marketing principles have been developed and applied mainly in the context of developed countries. This work contributes to the extension of such principles to an emerging economy with a public health problem related to overweight. Results of the research provide the basis to mold an appropriate intervention.